Skin to skin interactions. Does the infant massage improve the couple functioning? - Gnazzo, Antonio; Guerriero, Viviana; Di Folco, Simona; Zavattini, Giulio Cesare; de Campora, Gaia (Frontiers in Psychology, 2015)
Transition to parenthood is a critical stage of life due to several changes the couple has to handle. A large body of studies described how transition to parenthood can be linked to the onset of depressive symptoms, as well as the perception of a low social support, and an increased stress, representing a risk for the early mother—baby relationship. Infant Massage (IM) emerged as an helpful tool to improve maternal skills in interacting with the baby, and leading toward a decreasing of post partum symptoms. However, a growing body of literature highlights that men also may experience post-partum diseases, representing an additional risk for the development of the baby. To date, no study observed the impact of the infant massage on both partners. The aim of the current qualitative research is to observe the impact of the IM on a single couple of parents at childbirth. Pre (Time 1) and post-intervention (Time 3) procedure has been established to observe the changes occurring over the time in the couple. In particular, each member of the couple filled out the EPDS, the BDI-II, the MSPSS and the PSI-SF both at Time 1 and at Time 3. The treatment (Time 2) was represented by the IM training, and lasted 4 weeks. Findings revealed a decrease in depressive symptoms in both partners, as well as an improvement of their perception of stress related to parental role. No changes has been detected with respect to the perception of social support. The IM seems to be a helpful approach to prevent the establishment of pathological conditions in new parents. Although no direct measures on the child were used, the current qualitative data seem to suggest that the IM may represent a valuable tool to prevent the onset of early negative outcomes of the baby. Further investigations and empirical data are needed to improve the knowledge in this field.